Comparison of GOME‐2 UVA Satellite Data to Ground‐Based UVA Measurements in South Africa - (:unkn) unknown (My University, 2020)
Satellite estimates of surface ultraviolet A (UVA) (315–400 nm) from the Global Ozone Monitoring Experiment (GOME)‐2 were compared to ground‐based measurements at four stations in South Africa for 2015. The comparison of daily exposure and daily maximum irradiance was completed for all‐sky and clear‐sky conditions. There is a strong linear correlation between the satellite and ground‐based data with a correlation coefficient (r) between 0.86 and 0.97 for all‐sky conditions. However, at three of the stations the satellite data are underestimated compared to ground‐based data with a mean bias error (MBE) between −8.7% and −20.6%. A seasonal analysis indicated that there is a link between the bias in ground‐based and GOME‐2 UVA and cloud fraction. Factors such as aerosols, surface albedo, altitude and data resolution may contribute to the underestimations found at the three sites. These results indicate that satellite estimates of surface UVA over South Africa do not exhibit the same behavior as other stations around the world and therefore require further validation.
Keywords: African Research